Avaliação da implementação dos programas de atenção domiciliar nos hospitais estaduais localizados em Fortaleza-Ceará - Neri, Carmem Rita Sampaio de Sousa (2020)
In times of economic, political and social crises that the Brazilian population has been experiencing, one realizes the importance of public health services to find subsidies to improve care for chronic patients. Therefore, Home Care (HC) has been gaining prominence as an alternative for the continuity of assistance, with several benefits and the need for management and monitoring, to guarantee the objective that it proposes in the user's quality of life. The object of this research starts from the lack of knowledge about the implementation of home care in the health care network as a substitute for hospitalization, the main objective being to evaluate the answer to this question. It is a qualitative study, which touches the field of public policy evaluation, having a theoretical-methodological assumption in the narrative analysis for the construction of results. 17 semi-structured interviews were conducted with managers and health professionals from Home Care Programs linked to tertiary hospitals in the state of Ceará in Fortaleza, in addition to systematic observation of practices and search and analysis of management documents between the months of April to October 2019. The main results obtained in this research comprise the detailing of the process of implantation of Home Care Programs, the definition of the users' admission process and the eligibility criteria, in addition to dismissal, the performance of palliative care and the perception judicialization of health. Questions about the operationalization of Home Care Services, the health care network in which AD is inserted and the factors that facilitate and hinder the implementation of AD were elucidated by the narrative of the research participants. This investigation showed us in a complex way what Home Care is and how it is being implemented within the current health scenario of our State. We learned that the concept and practices of DA are intertwined, but nevertheless, it seeks improvement and adaptation based on the needs of the population and services.